2019
DOI: 10.1002/ecs2.2792
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific population dynamics of ocelots in Belize using open population spatial capture–recapture

Abstract: We used open population, spatial capture–recapture (SCR) models to estimate sex‐specific density, survival, per capita recruitment, and population growth rate of ocelots (Leopardus pardalis) at five sites in Belize with up to 12 yr of data per site. Open population SCR models enabled us to separate survival and recruitment from migration using an ecologically realistic, spatially explicit movement model. Yearly survival probability across 4 broadleaf forest sites was estimated at 0.73–0.84 for males and 0.81–0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…, similar again toSatter et al (2019). Our results of generation time (2.64 years) and the average litter size of 1.97 (range 1-3) were close to those of other studies in Europe.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…, similar again toSatter et al (2019). Our results of generation time (2.64 years) and the average litter size of 1.97 (range 1-3) were close to those of other studies in Europe.…”
supporting
confidence: 92%
“…However, we did not nd any strong difference in survival rates between sexes. A similar open population SCR study, conducted on a low-density ocelot population in Belize, also showed no signi cant differences in sex-speci c survival, despite a survival rate of 0.86 for females and 0.78 for males (Satter et al 2019). The authors suggested the statistical power was not enough to detect signi cant differences between sexes in these parameters, although they were able to determine sex for a large number of adult ocelots (n = 322).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, this camera spacing appears appropriate for ocelots. However, other studies attempting similar estimates for cats with differing body sizes, should pay careful attention to camera spacing relative to movement parameters of the target species (Satter et al , Satter ). Our cameras were spaced closer together than twice the estimated value of σ and produced sufficient numbers of spatial recaptures.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the sexes in home range size and ranging behavior (such as the avoidance of trail systems; e.g., Sollmann et al 2011 ) may result in sex-specific detectability by trail-based camera traps. Under these conditions, allowing g0 and σ to vary by sex in SCR models can improve the accuracy of density estimates ( Sollmann et al 2011 ; Tobler and Powell 2013 ; Satter et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%